Incidence of Dermatitis Herpetiformis in Sweden 2005 to 2018: A Nationwide Retrospective Cohort Study - Zeyad Albadri; Doua Al Bayati; Henrike Häbel; Sandra Jerkovic Gulin; Carina Grönhagen; Oliver Seifert (Medical Journals Sweden, 2023)
Dermatitis herpetiformis has been investigated in the past; however, only a limited number of studies have reported its incidence based on validated nationwide population-based registries. To address this gap, the aims of this study are to estimate the incidence of dermatitis herpetiformis in Sweden and to validate the National Patient Register (NPR) for diagnosis of dermatitis herpetiformis. A population-based open cohort study was conducted, including all patients diagnosed with dermatitis herpetiformis (International Classification of Diseases 10th revision; ICD-10 code L13.0) in Sweden from 2005 to 2018 (n = 1,724), identified from the NPR. The diagnosis of dermatitis herpetiformis in the NPR was validated using medical records, histopathological and immunopathological data, yielding a positive predictive value (PPV) of 62.5%. The mean annual incidence of dermatitis herpetiformis was 0.93/100,000 (95% confidence interval 0.79-1.08), female to male ratio 1:1, and mean age at diagnosis 60.9 years. In conclusion, this large nationwide cohort study showed a low validity for diagnosis of dermatitis herpetiformis in the NPR, and the adjusted incidence rate of dermatitis herpetiformis in Sweden was estimated to be 0.93/100,000, which is lower than that in previous Swedish studies.